[Comment] LigaSure versus conventional Milligan Morgan hemorrhoidectomy in Nigerian patients with symptomatic hemorrhoids - Huang Jian (结直肠肛门外科)
[Background] Hemorrhoidectomy is considered as the most effective approach for patients with grade Ⅲ and grade Ⅳ hemorrhoids; the operative procedure may be associated with significant postoperative pain and other complications. Several surgical techniques and devices have been developed to overcome these postoperative problems. [Objective] To compare perioperative and postoperative outcomes of hemorrhoidectomy performed with the LigaSure and the conventional Milligan-Morgan hemorrhoidectomy among Nigerian patients with symptomatic hemorrhoids. [Methodology] All consenting adult patients who fulfilled the inclusion criteria were randomized to either conventional Milligan-Morgan or LigaSure hemorrhoidectomy. Outcome measures were the duration of the procedure, estimated blood loss, and resolution of symptoms, which were assessed using the Sodergren hemorrhoids severity score (SHSS). Postoperative pain was evaluated using the visual analog scale (VAS), and the short-term recurrence rate was also checked at 3 months. Data were analyzed using the computer software IBM SPSS version 23. [Results] Fifty-two patients were randomized equally into the two arms. The median blood loss in the LigaSure group was 10.0 mL, whereas the median blood loss in the Milligan-Morgan group was 26.5 mL, (P＝0.0001). The median postoperative pain at 2 weeks using the VAS was 5.5 in the LigaSure group, and in the Milligan-Morgan group, it was 6.0 (P＝0.002). The mean duration of surgery in the LigaSure group was 18.04 min and 34.19 min in the Milligan-Morgan group (P＝0.0001). [Conclusion] LigaSure hemorrhoidectomy is faster and associated with less blood loss compared to conventional Milligan-Morgan hemorrhoidectomy.